PC-based gamma knife radiosurgery dose calculation. - Tseng, Y.J (IEEE Engineering in medicine and biology magazine)
The PC-based dose-calculation system designed for gamma knife radiosurgery introduced in this article delivers desired accuracy and is equipped with a friendly graphical user interface to allow foolproof operations. With the ongoing advancement in PC technology, the performance/cost ratio is expected to continue to rise to render more incentive in developing a PC-based dose-calculation system.